1989
DOI: 10.1128/aem.55.9.2385-2390.1989
|View full text |Cite
|
Sign up to set email alerts
|

Survey of metal tolerance in moderately halophilic eubacteria

Abstract: The tolerance patterns, expressed as MICs, for 250 moderately halophilic eubacteria to 10 heavy metals were surveyed by using an agar dilution method. The moderate halophiles tested included 12 culture collection strains and fresh isolates representative of Deleya halophila (37 strains), Acinetobacter sp. (24 strains), Flavobacterium sp. (28 strains), and 149 moderately halophilic gram-positive cocci included in the genera Marinococcus, Sporosarcina, Micrococcus, and Staphylococcus. On the basis of the MICs, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(48 citation statements)
references
References 23 publications
4
42
0
1
Order By: Relevance
“…are able to grow at high bioavailable concentrations of As. Nieto et al [44] and Deshpande et al [45] have similarly found that Acinetobacter strains were highly resistant to various metals and that several Acinetobacter spp. were commonly found at metal-contaminated sites.…”
Section: Discussionmentioning
confidence: 97%
“…are able to grow at high bioavailable concentrations of As. Nieto et al [44] and Deshpande et al [45] have similarly found that Acinetobacter strains were highly resistant to various metals and that several Acinetobacter spp. were commonly found at metal-contaminated sites.…”
Section: Discussionmentioning
confidence: 97%
“…The agar dilution method was used to determine the bacterial resistance to toxic metals (Washington and Sutter 1980). Various concentrations of heavy metals (0AE05, 0AE01, 0AE1, 0AE5, 1AE0, 1AE5, 2AE0, 2AE5, 5AE0, 7AE0, 9AE0, 10AE0, 20AE0 and 40AE0 mmol l )1 ) were examined as in a previous study on metal tolerance of moderately halophilic eubacteria (Nieto et al 1989). The appropriate concentrations of heavy metals were added to 100-ml Erlenmeyer flasks containing 20-ml nutrient agar medium and 1AE0 mol l )1 NaCl as the optimal concentration for strain MA2 growth.…”
Section: Determination Of Toxic Metal Resistancementioning
confidence: 99%
“…Very few studies on the interactions of moderate halophiles with toxic metals have been reported (Onishi et al 1984). Such information is desirable because some of these metal-resistant halophilic bacteria could be used as bioassay indicators in saline aquatic polluted environments (Nieto et al 1989). Recently, copper uptake was investigated in halophilic bacteria isolated from the Dead Sea shore in Jordan: copper ions were found to accumulate in the cell wall or between the cell wall and the plasma membrane (Fouad et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity to heavy metals such as Al, Cu, and Zn was assayed on AN medium because it had been shown previously that metal toxicity can be heavily influenced by environmental factors such as pH, clay minerals, and inorganic anionic and cationic components (Babich & Stotzky, 1980). In general, media containing salts, such as minimal media, lead to a decreased sensitivity to heavy metals (Nieto et al, 1989). Our results showed that the PBP mutant displayed an enhanced sensitivity to KCl and LiCl, compared with the wild-type strain, because its growth was severely reduced and completely inhibited by these salts at 300 and 400 mM, respectively (Table 2).…”
Section: Ionic-and/or Hyperosmotic-stress Conditions Alter the Survivmentioning
confidence: 99%